The effectiveness of using the educational video in teaching the kindergarten child to pronounce the Arabic letters compared to the Norani rule - Ghabashneh, Musab Ahmed Khalifa Lafi (Journal of Educational and Psychological Sciences, 2022)
This study aimed at measuring the effectiveness of the use of educational video when teaching Al-Qaida Al-Nooraniah in providing the kindergarten child with the correct pronunciation of the Arabic letters. The first is experimental, the number of its members is (30), and the second is control, and the number of its members is (30) children from kindergartens in Jordan. The researcher used as a study tool the educational video, an oral test, a written test, and the study concluded that the experimental group was superior in pronunciation skills compared to the control group. There are statistically significant differences at the level of the function (α≤0.05) in the children's use of the educational video that includes the light rule on their achievement in pronunciation of letters in the Arabic language subject.
Keywords: Educational video; Al-Qaida Al-Nooraniah; pronunciation of letters; kindergarten